A elisão fiscal no estado democrático de direito : entre o dever fundamental de pagar tributos e a liberdade de organização privada dos negócios - Hilgert, Enaide Maria (2012)
The research s main objective is to examine the problem of tax avoidance in face of values, principles and rules that establish the Democratic Rule-of-Law State . Although the Federal Constitution guarantees to the individual the fundamental right to freely organize private business, which in the tax legal area is known as tax planning , there is the fundamental duty of paying taxes as an opposing point, following the reasoning of the individual s contributive capacity. In the model of Fiscal State, the compliance of the fundamental duty of payment of taxes is essential to the financial support of the government apparatus and, specially, to the promotion and finance of fundamental rights. Under this view, tax avoidance, which consists in reducing sums of due taxes, or even in attempts to completely avoid tax incidence, shall not be legitimate if the tax planning procedures are abusive. Intending to Grant to the Treasury a specific tool to fight abusive tax planning, a general anti avoidance law was introduced in the National Tax Code. The effect of the this law depends on the publication of an additional ordinary law that will discipline the procedures to be observed by the public administration when refuting acts and businesses practiced with intent to dissimulate operations that generate tax or disguise the nature of elements that constitute tax obligation. Even with limited effect, the enactment of the anti avoidance general law in the Brazilian legal order, along with the construe of the Tax Law in accordance to the Jurisprudence of Values, in a certain way, influenced the decisions of administrative proceedings related to tax planning operations. Since 2005, the decisions of The Taxpayer s Counsel, later, The Administrative Council of Fiscal Appeals - CARF, require a motive beyond taxes or an actual business purpose to sustain the tax avoidance obtained with operations under tax planning.